OPTIMASI PEMANFAATAN AIR DI DAERAH IRIGASI TANGGUL KABUPATEN PASURUAN MENGGUNAKAN PROGRAM LINIER - Retnowati, Fitri; Sayekti, Rini Wahyu (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
ABSTRACT: The utilization of water resources for irrigation requirements influenced by climate change. In the long time, climate variability and diversity will seasoon change. As a result of season change, water balance had in excess condition (surplus) or lack condition (deficit). Therefore, optimization is needed to optimize the utilization of irrigation water as well as adjustment plan cropping layouts can make maximum agriculture profits and resolve unbalanced water balance. Water balance analysis uses two debits, dependable discharge 80% and dependable discharge 50%. This study uses seven alternatives in optimization model based on existing cropping area of 728 ha. The optimization technic that used in this study is Linear Programming which is converted to mathematic model. Software Solver used to help in the determination of objective function which will be maximized agricultural production at growing season is Z = C1X1 + C2X2 + C3X3 + .... + CnXn with conclusion variable are cropping land area (X1, X2,  X3, .... Xn). Where constrain variables are volume of discharge (Vpdn.Xna + Vpjn.Xnb + Vtn.Xnc ≤ Vsn)  and land area (Xna + Xnb + Xnc ≤ Xt). From the water balance analysis, dependable discharge 50% is chosen because approached/represented existing of discharges in Tanggul’s irrigates area for last ten years (2007 until 2016). Selected cropping layouts by changing cropping schedule are rice, corn, sugarcane-rice, soybean, sugarcane-rice, peanut, sugarcane. Before optimization, the existing cropping intensity is 287,5%. From the optimization result for dependable discharge 50% (existing of discharges) based on the layout of cropping plan was chosen with cropped intensity for a year in amount 300% and profit in amount Rp. 95.438.280.000,-. Keywords: irrigation, water balance, optimization, cropped intensity, agriculture profit